Pengembangan Lembar Kerja Siswa Berbasis Lingkungan Hidup untuk Meningkatkan Keterampilan Menulis Siswa SD - vit ardhyantama (Universitas Pendidikan Indonesia (UPI), 2021)
This research aims to discribe the development, the effectiveness and The result of developing students’ worksheet based on environment living to increase their writing skill. This paper applies research and development (RD) method which is 4D development model based on S.Thiagarajan (1974). The product is tested to 4 students at fourth graders of elementary school in small group. The product eligibility is based on the results of the assessment of material experts, media experts, learning experts, and the responses of fourth graders in elementary school as test subjects. The technique of collecting data use observation, interview, questionnaire, portfolio test, and documentation. The technique of analyzing data use product validity and test. The result of this paper shows that: The media is stated effective based on the achievement of mastery leaning students who reach more than 75, amounting to 85%.